A study on the sulphuric acid leaching of copper converter slag in the presence of dichromate - Altundoğan, Hamdi Soner; Boyrazlı, Mustafa; Tümen, Fikret (My University, 2004)
In this study, extraction characteristics of Cu, Co, Zn and Fe from copper converter slag by oxidative leaching with potassium dichromate–sulphuric acid lixiviant were investigated. The experimental results indicated that the presence of dichromate has a large influence on the extraction of metals. Cu recovery seems to be feasible by leaching with a lixiviant containing potassium dichromate and sulphuric acid because of high Cu extractions and low Fe concentrations in pregnant liquor. Also, copper extraction yields increased by increasing the dichromate concentration while Co, Zn and Fe extractions considerably decreased.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Extractive metallurgy; Hydrometallurgy; Leaching; Oxidation